Decentralization of Education in Indonesia: Problems of Implementation - Nuril Huda (Universitas Negeri Malang, 2016)
Desentralization of education is intended to achieve efficiency in education by accommodating aspiration of local communities. Reports on the implementation of a pilot project of desentralization suggest that it is not as easy as expected in its implementation. The problems include legal aspects that need to be revised, unrediness of the region to take over the new responsibilities, attitude of the central authorities, and perception on the concept and goal of decentralization. Suggestions to improve its implementation include participatory approach, comprehensive planning, and building capacity of stakeholders